A sonar-embedded disguised communication strategy by combining sonar waveforms and whale call pulses for underwater sensor platforms. (February 2019) - Jiang, Jiajia; Wang, Xianquan; Duan, Fajie; Fu, Xiao; Huang, Tingting; Li, Chunyue; Ma, Ling; Bu, Lingran; Sun, Zhongbo
Abstract: The security and covertness are very important for underwater sensor platforms, especially for underwater military sensor platforms. In this paper, different from the conventional low probability of intercept detection and communication methods which generally relies on the low signal-noise-ratio (SNR) or changed-parameters, a sonar-embedded disguised communication strategy for underwater sensor platforms is explored by combining the chirp sonar waveforms and sperm whale call pulses. In the presented strategy, to achieve the target detection, the conventional sonar waveforms (e.g. chirp) are selected. To accomplish covert communication, the original sperm whale clicks are nicely utilized. Then the selected sonar waveform and the utilized original clicks are superimposed together to form a combination waveform to synchronously complete underwater target detection and covert communication functions. Because the clicks of whales are almost always classified into ocean noises and filtered out, the covert communication is achieved depending on this disguised strategy. Simulations demonstrate the feasibility of sonar-embedded covert communication.